Reconstructing the Ultimum Remedium Principle in Environmental Criminal Law: Toward a Primum Remedium Approach Based on Ecological Justice - Ahmad Mubarak; Ifrani Ifrani; Rahmida Erliyani; Mispansyah Mispansyah (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2026)
The accelerating environmental crisis has exposed the limitations of an anthropocentric legal paradigm that continues to subordinate ecological sustainability to economic development. Within this context, the continued reliance on the ultimum remedium principle in environmental criminal law has become increasingly contested, as treating criminal sanctions as a measure of last resort often weakens deterrence and delays effective responses to serious environmental harm. Despite growing concern over environmental law enforcement, limited attention has been given to the conceptual incompatibility between the ultimum remedium doctrine and the distinctive characteristics of environmental offences. This study critically examines that incompatibility and develops a reconstruction model based on primum remedium and ecological justice. Employing normative legal research through statutory and conceptual approaches, the study analyzes legislation, legal doctrine, and theories of criminal law policy, legal systems, and law as a tool of social engineering. The findings demonstrate that ultimum remedium is ill-suited to environmental crimes that are collective, cumulative, and frequently irreversible, while Indonesia's reliance on administrative enforcement diminishes the preventive function of criminal law. This study contributes to environmental criminal law scholarship by proposing an ecological justice framework that repositions criminal law as the primary response to serious environmental offences while preserving proportionality and legal certainty.